Extending resectability of hilar cholangiocarcinomas: how can it be assessed and improved?. (31st October 2018) - Donati, Marcello; Stang, Axel; Stavrou, Gregor A; Basile, Francesco; Oldhafer, Karl J
Until the 1980's, Klatskin tumors were considered 'desperate cases' and most of them were not resected; almost no oncologic concept was available. After many improvements, today, extended hepatectomy, including caudate lobe resection and lymphoadenectomy, have become a standard of care for oncologicaly radical resection of Klatskin tumors. Portal vein en bloc resection, if necessary, is a diffused standard assuring R0-resection without any improvement of survival in most series. Arterial resection remains episodical and controversial in its oncologic impact. Arterial resection-reconstruction was demonstrated to be feasible with many different technical possibilities. Neoadjuvant chemotherapy, refinement of associating liver partition and portal vein ligation for staged hepatectomy and liver transplantations are some possible future resources for treatment of those aggressive tumors that could be able to expand the pool of treatable patients. Graphical abstract: